Current recommendations and novel strategies for sustainable management of soybean sudden death syndrome - Rodríguez, María C. (2021)
Fil: Fil: Rodríguez,María C. Instituto de Agrobiotecnología y Biología Molecular, CICVyA. Instituto Nacional de Tecnología Agropecuaria (CONICET). Argentina.